1999
DOI: 10.1148/radiology.213.2.r99nv19573
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pancreatocutaneous Fistula after Percutaneous Drainage of Pancreatic Fluid Collections: Role of Cause and Severity of Pancreatitis

Abstract: Development of PPCF correlated with severity of pancreatitis, regardless of the cause of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 30 publications
0
61
0
1
Order By: Relevance
“…Diagnosis was the presence of gas in the peripancreatic collection on CT or a positive culture at fineneedle aspiration. The etiology of infected pancreatitis necrosis was reported in 9 studies [8,16,17,25,27,28,[33][34][35], in which the most common cause was biliary tract disease. APACHE II scores and CT severity index scores were used in the 10 studies [8,16,17,28,29,31,[33][34][35][36]; 0.195 (55.3 %) of 352 patients had organ failure before PCD in 9 studies (including single and multiple organ failure) [8,17,29,30,[32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Diagnosis was the presence of gas in the peripancreatic collection on CT or a positive culture at fineneedle aspiration. The etiology of infected pancreatitis necrosis was reported in 9 studies [8,16,17,25,27,28,[33][34][35], in which the most common cause was biliary tract disease. APACHE II scores and CT severity index scores were used in the 10 studies [8,16,17,28,29,31,[33][34][35][36]; 0.195 (55.3 %) of 352 patients had organ failure before PCD in 9 studies (including single and multiple organ failure) [8,17,29,30,[32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the mean length of hospital stay [16,[27][28][29][31][32][33], which ranged from 3 to 241 days. Eight studies reported the mean length of initial treatment with PCD after hospital admission [8,16,17,25,28,29,32,35]. The success rate of PCD, defined as the recovery of patients without additional surgical intervention, was 56.2 % (324 of 577 patients).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations